MALFORMAÇÃO CONGÊNITA NO HOSPITAL GERAL DO ESTADO DE ALAGOAS: RELATO DE CASO - Omena, Laís; Silva, Lucinelma; Nanes, Gabriela; Rocha, Dayana; Vieira, Natália (Gep News, 2019)
Trabalho apresentado durante o I MASMI